2015
DOI: 10.1007/s13277-015-3133-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived chemokine CCL22 and regulatory T cells in ovarian cancer patients

Abstract: The study was undertaken to evaluate macrophage-derived chemokine (CCL22) levels in the peritoneal fluid (PF) and plasma of patients with ovarian cancer (n = 93) in relation to regulatory T cells (Tregs; n = 75). The peritoneal fluid CCL22 concentrations were significantly higher in epithelial ovarian cancer (EOC) patients than in patients with benign tumors-serous cystadenoma (n = 32). There was no difference in plasma levels of CCL22 in EOC patients compared with the non-cancer and healthy volunteers (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…): IL‐1β (120.5 ± 9.7‐fold), IL‐1α (54.5 ± 10.1‐fold), IL‐6 (42.5 ± 3.4‐fold), CCL22 (59.2 ± 1.5‐fold), CCL17 (130.8 ± 1.5‐fold), and MMP12 (503.2 ± 2.5‐fold). Among them, CCL22, CCL17, IL‐6, and IL‐1β are well‐known pro‐tumoral cytokines that are able to stimulate tumor cell proliferation and invasion, as well as promote the suppression of antitumor immune responses . This study found that FAK inhibitor‐induced cell multinucleation resulted in a dramatic increase in several pro‐tumoral cytokines, suggesting the possibility of macrophages becoming pro‐tumoral.…”
Section: Discussionmentioning
confidence: 70%
“…): IL‐1β (120.5 ± 9.7‐fold), IL‐1α (54.5 ± 10.1‐fold), IL‐6 (42.5 ± 3.4‐fold), CCL22 (59.2 ± 1.5‐fold), CCL17 (130.8 ± 1.5‐fold), and MMP12 (503.2 ± 2.5‐fold). Among them, CCL22, CCL17, IL‐6, and IL‐1β are well‐known pro‐tumoral cytokines that are able to stimulate tumor cell proliferation and invasion, as well as promote the suppression of antitumor immune responses . This study found that FAK inhibitor‐induced cell multinucleation resulted in a dramatic increase in several pro‐tumoral cytokines, suggesting the possibility of macrophages becoming pro‐tumoral.…”
Section: Discussionmentioning
confidence: 70%
“…As shown in Fig. 5A-C, in example FACS plots generated under each culture condition and 5D where Tregs are quantified, exposure to Ccl22 did not induce a greater Treg compartment among splenocytes at any tested concentration, even at higher than physiologic (serum) concentrations (21). However, comparing TGF-β treatment to untreated cells indicates a significant treatment effect by ANOVA ( P =0.0002), and the % of Treg is significantly different from untreated samples (P<0.05) at both 2 and 20 ng/mL using Dunnett's multiple comparison post-test.…”
Section: Resultsmentioning
confidence: 84%
“…Other significantly down regulated genes that play a role in regulation of stromal cell components include FOS, EGR2, CREB-5, IL-6, Map2K1, among others (table S-1). At day 5, genes such as CCL22 [43], TIMD4 [44] and CCL19 [45], associated with macrophage networks were significantly down regulated.…”
Section: Resultsmentioning
confidence: 99%